Cycling‐induced recurrent spontaneous pneumomediastinum and pneumopericardium in a young female patient. Issue 3 (20th March 2022) - Herrmann, Anna; Herrmann, Matthias; Passlick, Bernward; Herth, Felix; Herrmann, Johannes
Abstract: We present an exceptional case of recurrent cycling‐induced spontaneous pneumomediastinum and pneumopericardium in a female patient without any trauma. Radiological and endoscopic examinations were carried out to exclude other differential diagnoses. Decision for in‐hospital observation and conservative treatment was made. No symptoms were reported 12 months after return to sports activity. Abstract : Spontaneous pneumomediastinum and pneumopericardium should be considered as rare differential diagnosis in athletes presenting with chest pain following intensive bike training. Radiological and endoscopic examinations seem reasonable to exclude life‐threatening conditions. Conservative treatment may be favored, and patients may return to regular sports activity after appropriate education.